Molecular Interaction of Acetylcholinesterase with Carnosic Acid Derivatives: A Neuroinformatics Study - Merad, M.; Soufi, W.; Ghalem, S.; Boukli, F.; Baig, M.H.; Ahmad, K.; A. Kamal, Mohammad (CNS & Neurological Disorders - Drug Targets, 2014)
Alzheimer's disease is a progressive degenerative disease of the brain marked by gradual and irreversible declines in cognitive functions. Acetylcholinesterase (AChE) plays a biological role in the termination of nerve impulse transmissions at cholinergic synapses by rapid hydrolysis of its substrate,
Keywords: carnosic acid derivatives